2015
DOI: 10.1097/ede.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Application of Latent Variable Methods to the Study of Cognitive Decline When Tests Change over Time

Abstract: Background The way a construct is measured can differ across cohort study visits, complicating longitudinal comparisons. We demonstrated the use of factor analysis to link differing cognitive test batteries over visits to common metrics representing general cognitive performance, memory, executive functioning, and language. Methods We used data from three visits (over 26 years) of the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS) (N=14,252). We allowed individual tests to contribute inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…Three of these tests were also administered at visit 2. Latent variable methods were used to summarize these tests into a factor score representing general cognitive performance[8]. Scores were standardized such that a factor score of 1 represents general cognition that is 1 standard deviation above the mean.…”
Section: Methodsmentioning
confidence: 99%
“…Three of these tests were also administered at visit 2. Latent variable methods were used to summarize these tests into a factor score representing general cognitive performance[8]. Scores were standardized such that a factor score of 1 represents general cognition that is 1 standard deviation above the mean.…”
Section: Methodsmentioning
confidence: 99%
“…Using data from these tests in a factor analysis, factor scores for general cognitive performance, executive functioning/processing speed, memory and language were derived. 22 Briefly, factor analysis is a structured approach for identifying common covariation between specific indicators, in this case the cognitive tests, to reduce measurement error when combining data across multiple cognitive tests. The interpretations of factor scores are similar to that for z scores because they were scaled to have a mean of 0 and variance of 1 at ARIC visit 2 when the participant’s cognitive function was first tested.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, by fitting an IRT‐graded response model to a calibration sample we allowed the relevant MFQ and harmonized PHQ‐2 items to be differently related to the underlying construct of depression—including DIF by study on one item. This is a substantial improvement over other potential methods that are used for scoring such as proportion, sum or z ‐score (Curran et al ., ; Gorter et al ., ; Griffith et al ., ; Gross et al ., ). Next, IRT longitudinal equating through incorporation of known item parameters for the harmonization and scoring of longitudinal and cross‐sectional ordinal data together with latent growth models, such as a piecewise linear model, were demonstrated that they can be implemented simultaneously.…”
Section: Discussionmentioning
confidence: 97%